On the Origins of Fracture Toughness in Advanced Teleosts: How the Swordfish Sword's Bone Structure and Composition Allow for Slashing under Water to Kill or Stun Prey. Issue 12 (2nd May 2019) - Schmidt, Felix N.; Zimmermann, Elizabeth A.; Walsh, Flynn; Plumeyer, Christine; Schaible, Eric; Fiedler, Imke A. K.; Milovanovic, Petar; Rößle, Manfred; Amling, Michael; Blanchet, Clément; Gludovatz, Bernd; Ritchie, Robert O.; et al.
Abstract: The osseous sword of a swordfish ( Xiphias gladius ) is specialized to incapacitate prey with stunning blows. Considering the sword's growth and maturation pattern, aging from the sword's base to the tip, while missing a mechanosensitive osteocytic network, an in‐depth understanding of its mechanical properties and bone quality is lacking. Microstructural, compositional, and nanomechanical characteristics of the bone along the sword are investigated to reveal structural mechanisms accounting for its exceptional mechanical competence. The degree of mineralization, homogeneity, and particle size increase from the base toward the tip, reflecting aging along its length. Fracture experiments reveal that crack‐growth toughness vastly decreases at the highly and homogeneously mineralized tip, suggesting the importance of aging effects. Initiation toughness, however, is unchanged suggesting that aging effects on this hierarchical level are counteracted by constant mineral/fibril interaction. In conclusion, the sword of the swordfish provides an excellent model reflecting base‐to‐tip‐wise aging of bone, as indicated by increasing mineralization and decreasing crack‐growth toughness toward the tip. The hierarchical, structural, and compositional changes along the sword reflect peculiar prerequisites needed for resisting high mechanical loads. Further studies on advanced teleosts bone tissue may help to unravel structure–function relationships of heavily loaded skeletons lacking mechanosensing cells. Abstract : The osseous sword of the swordfish reveals a lengthwise aging pattern reflected by mineralization and toughness indices. The mineralization (low at base, high at tip) is linked to specific mechanical competence of the bone material, lacking mechanosensitive osteocytes known to initiate repair processes in humans. Thus, the swordfish presents an intriguing model to study anosteocytic mechanisms of bone quality maintenance.